Innovative AE and NDT techniques for on-site measurement of concrete and masonry structures : State-of-the-Art Report of the RILEM Technical Committee 239-MCM /: State-of-the-Art Report of the RILEM Technical Committee 239-MCM. (2016) - Unknown
No abstract available